Nonlinear mode competition in a lasing nanoplasmonic metamaterial - Wuestner, S.; Hamm, J.M.; Pusch, A.; Renn, F.; K. L. Tsakmakidis; Hess, O. (Optics InfoBase Conference Papers, 2012)
Active nanoplasmonic metamaterials, pumped above lasing threshold, can exhibit dynamic competition between bright, radiative and dark, trapped modes of the structure. We study the spatio-temporal mode competition and explore methods of mode control. © 2011 Optical Society of America.